Leukemia Stem Cell Release From the Stem Cell Niche to Treat Acute Myeloid Leukemia - Villatoro, Alicia; Konieczny, Joanna; Cuminetti, Vincent; Arranz, Lorena (Frontiers in Cell and Developmental Biology, 2020)
Acute myeloid leukemia (AML) is a heterogeneous, complex and deadly disease, whose treatment has hardly evolved for decades and grounds on the use of intensive chemotherapy regimens. Chemotherapy helps reduce AML bulk, but promotes relapse in the long-run by selection of chemoresistant leukemia stem cells (LSC). These may diversify and result in progression to more aggressive forms of AML. In vivo models suggest that the bone marrow stem cell niche helps LSC stay dormant and protected from chemotherapy. In this context, the purpose of this review is 1) to summarize relevant changes in stem cell niche homing and adhesion of AML LSC versus healthy hematopoietic stem cells, 2) to provide an overview of recent and current clinical trials aiming at targeting these processes for AML treatment, and 3) to provide the basis for future directions within this field. Promising results with various nonmutation-targeted novel therapies directed to LSC eradication via interference with their anchoring to the stem cell niche have encouraged on-going or future advanced phase III clinical trials. In the coming years, we may see a shift in the focus of AML treatment to LSC-directed therapies if the prospect of improved cure rates holds true. In the future, AML treatment should lean towards personalized therapies using combinations of these compounds plus mutation-targeted agents and/or targeted delivery of chemotherapy, aiming at LSC eradication with reduced side effects.